2021
DOI: 10.3390/ani11102806
|View full text |Cite
|
Sign up to set email alerts
|

Objective Video-Based Assessment of ADHD-Like Canine Behavior Using Machine Learning

Abstract: Canine ADHD-like behavior is a behavioral problem that often compromises dogs’ well-being, as well as the quality of life of their owners; early diagnosis and clinical intervention are often critical for successful treatment, which usually involves medication and/or behavioral modification. Diagnosis mainly relies on owner reports and some assessment scales, which are subject to subjectivity. This study is the first to propose an objective method for automated assessment of ADHD-like behavior based on video ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Only a few canine behaviour studies to date applied machine-learning mediated tracking, most of them using tracking based on a single camera (e.g., Barnard et al, 2016;Bleuer-Elsner et al, 2019;Fux et al, 2021;Karl et al, 2020;Zamansky et al, 2018). These studies provided evidence that dogs with a deprivation syndrome moved less compared to normal controls when presented with a robot dog (Zamansky et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few canine behaviour studies to date applied machine-learning mediated tracking, most of them using tracking based on a single camera (e.g., Barnard et al, 2016;Bleuer-Elsner et al, 2019;Fux et al, 2021;Karl et al, 2020;Zamansky et al, 2018). These studies provided evidence that dogs with a deprivation syndrome moved less compared to normal controls when presented with a robot dog (Zamansky et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Intensity of use is an animal movement metric used in ( 47 ). We decided to include this feature due to its usefulness in ( 30 ) in the context of dog behavior analysis.…”
Section: The Clustering Methodsmentioning
confidence: 99%
“…We decided to include this feature due to its usefulness in (30) in the context of dog behavior analysis. 3.…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing previous studies on dog behavior recognition, we identified related studies [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], which are summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%